PENDAMPINGANHUKUMHAK PEKERJA (USIA PRODUKTIF)BERDASARKANHUKUM KETANAGAKERJAAN - Unggul Priyadi (Asian Journal of Innovation and Entrepreneurship, 2013)
Labor is any person who is able to work in order to produce goods and servicesbetter meet the needs of themselves and for others. Society in life requires the name ofthe job in order to meet the basic needs / primer. The legal protection of workers canbe realized to the fullest through the role of government, where the government has theauthority to establish regulations concerning the rights and obligations of the employer,because without the presence of state workers' rights are particularly vulnerableviolated. legal protection, maintenance and improvement of welfare are maintained inthe form of workers' social security program which is the basis, the basis of kinship andmutual assistance.